Mediating effects of satisfaction in the relationship between motivation factors and continuous viewing intentions towards Chinese documentary programs - Mengyu, Li (2023)
Chinese documentary programs are the true reflection and portrayal of the reality of Chinese culture, economy, and society. The Chinese government encouraged television stations and documentary production teams to create more excellent works. Also, the broadcasting platforms of Chinese documentary programs have been effectively guaranteed. Nowadays, however, compared with other programs in the same day-period, the ratings of Chinese documentary programs on television stations are slumping. Although the government, television stations and video websites have invested a lot of energy and services in terms of policies, funds and creative talents to support Chinese documentary programs, the dilemma still cannot be solved. Prior studies have mainly analysed the content and narrative of Chinese documentary programs. However, a very limited number of studies have been conducted from the perspective of audience, such as factors influencing their viewing intentions, satisfaction level and so forth. Furthermore, using the theory of uses and gratification to investigate undergraduate students’ viewing intention to Chinese documentary programs is rare as well. Therefore, this research was conducted to examine the factors predicting undergraduates’ continuous viewing intentions towards Chinese documentary programs. Uses and gratification theory and agenda-setting theory were applied to identify factors contributing to audiences’ continuous viewing intentions. Based on the content of adopted theories, viewers’ cognitive needs, affective needs, tensionfree needs, and public perception were testified as motivating factors. Mixed methods were performed to achieve research objectives. In the first phase, a quantitative survey was conducted by adopting a self-administered questionnaire. All variables were measured by scales previously used by other scholars. Convergent and discriminant validity of the scale were examined using Confirmatory Factor Analysis. The data analysis was conducted with SEM on 549 undergraduates from Zhengzhou University, mainland China. In the second phase, a qualitative method was performed to identify 15 informants from quantitative data analysis. A thematic analysis was used to interpret the data from a semi-structured interview. Quantitative and qualitative results altogether demonstrated that cognitive needs, affective needs, tensionfree needs, and public perceptions could influence audiences’ continuous viewing intentions towards Chinese documentary programs. Meanwhile, the factors of gender, age, and the year of study indicated significant effects on continuous viewing intentions among all socio-demographic factors except for subjects. At last, satisfaction as a mediating variable showed a significant effect. This research contributed to provide a new perspective to understand the theory of uses and gratification by introducing the public perceptions from agenda-setting theory as an independent variable and also by solving specific research questions using mixed methods. Moreover, various practical implications for policymakers and media practitioners (such as broadcasters, video websites, documentaries producing teams, etc.) were further discussed.